2008
DOI: 10.1016/j.mito.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of mitochondria by 10-N-alkyl acridine orange analogues: Role of alkyl chain length in determining cellular uptake and localization

Abstract: Abstract10-N-nonyl acridine orange (NAO) is used as a mitochondrial probe because of its high affinity for cardiolipin (CL). Targeting of NAO may also depend on mitochondrial membrane potential. As the nonyl group has been considered essential for targeting, a systematic study of alkyl chain length was undertaken; three analogues (10-methyl-, 10-hexyl-, and 10-hexadecyl-acridine orange) were synthesized and their properties studied in phospholipid monolayers and breast cancer cells. The shortest and longest al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…Whatever the mechanism(s) involved, these results demonstrate strong alterations of mitochondrial biogenesis and activity in cls1 mutant plants. However, the presence of at least partially functional mitochondria, in particular giant mitochondria, is indicated by the accumulation of membrane potential-sensitive dyes and NAO (Figure 4), showing that this dye is definitely not specific for CL, as demonstrated previously in yeast (Gohil et al, 2005a;Rodriguez et al, 2008;Mileykovskaya and Dowhan, 2009).…”
Section: Discussionsupporting
confidence: 61%
“…Whatever the mechanism(s) involved, these results demonstrate strong alterations of mitochondrial biogenesis and activity in cls1 mutant plants. However, the presence of at least partially functional mitochondria, in particular giant mitochondria, is indicated by the accumulation of membrane potential-sensitive dyes and NAO (Figure 4), showing that this dye is definitely not specific for CL, as demonstrated previously in yeast (Gohil et al, 2005a;Rodriguez et al, 2008;Mileykovskaya and Dowhan, 2009).…”
Section: Discussionsupporting
confidence: 61%
“…The calorimetry and fluorimetry data for NAO and PL mixtures described in this paper highlight the limitations of using NAO to make quantitative statements regarding CL in membranes (41,43,44). We found that NAO binds to anionic PLs promiscuously and displays spectroscopic changes that are inconsistent with a unique interaction between NAO and CL.…”
mentioning
confidence: 72%
“…Studies of the interaction of NAO with CL in mitochondrial membranes have not been particularly relevant to E. coli, since CL is the major anionic PL in mitochondria, whereas PG is the most abundant anionic PL in E. coli; the interaction of PG with NAO under physiological conditions remains unstudied. Several research groups have noted discrepancies with the use of NAO, primarily in its lack of specificity in both mitochondria (39,(41)(42)(43) and archaea (44). Here, we quantitatively study the organization of anionic PLs in E. coli cells using a combination of biophysical, microscopic, and mass spectrometric techniques.…”
Section: G Enome-wide Studies Of Bacillus Subtilis Escherichia Colimentioning
confidence: 99%
“…191–193 Different alkyl chain lengths were tested for such purpose, and the conclusion is that the efficiency of cellular staining is increased with a longer alkyl chain but the target selectivity is compromised. 194,195 Because the probe is cationic, its cellular accumulation was demonstrated to be a function not only of mitochondrial mass and cardiolipin content but also of the mitochondrial membrane potential. 172,196 …”
Section: Transport Of Small Cationic Compounds and Biomolecules Tomentioning
confidence: 99%